The habitat and the socio-environmental vulnerability in the Reina community of the Cienfuegos city (Islas, 2022)
ABSTRACT: Introduction: The present research addresses the study of how socio-environmental vulnerability and habitat quality are related in the Reina community in the city of Cienfuegos. In accordance with this problem, the general objective was proposed as follows: to analyze the relationship between socio-environmental vulnerability and habitat quality in the Reina community in the city of Cienfuegos. Methods: For the development of the research, the mixed methodological principle has been used, relying on techniques such as non-participant observation, structured interview and in-depth interview, document analysis, survey to adequately develop the work and the SWOT Matrix in which it is intended to know the internal and external problems of the community. Results: The socio-environmental vulnerability in the Reina community is determined by the abandonment of the environment. There is, in some cases, ignorance towards these problems, according to the analysis of results. Conclusions: Its threats and weaknesses should be mitigated from its potentialities, through the establishment of lines of action with criteria of measures and possible projects to be carried out to give solution to these problems.
Keywords: vulnerability; socio-environmental vulnerability; habitat; Reina